Strengthening the Small and Medium Enterprise Sector by Switching to Bills and Notes - Szalay, Zsuzsanna; Vértesy, László; Novák, Zsuzsanna (Public Finance Quarterly, 2020)
The proposal to switch to bills and notes might be shocking. The fact that Act CLXXXV of 2017 on the Regulations for Bills of Exchange and Promissory Notes entered into effect in Hungary on 1 January 2018 in order to enforce the uniform regulations pertaining to the legislation on bills of exchange and promissory notes, yet we still cannot talk about the issuance and use of bills and notes, is just as odd. In our study, we argue that in the absence of other short-term corporate securities, bills and notes could help the liquidity management of SMEs owing to their elaborated legal background. We briefly present the importance of corporate securities in the financing of companies both on domestic and international level, as well as the evolution of financial services related to bills and notes in the mirror of the statistics of the Hungarian supervisory authority, and we also provide possible ways for developing the financial services related to bills and notes. We review the previous and current Hungarian legal-regulatory environment of bills and notes and then summarise the arguments for their use in Hungary.